2022
DOI: 10.1016/j.contraception.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review exploring the contraception values and preferences of sex workers, transmasculine individuals, people who inject drugs, and those living in humanitarian contexts

Abstract: Ping Teresa Yeh , A systematic review exploring the contraception values and preferences of sex workers, transmasculine individuals, people who inject drugs, and those living in humanitarian contexts, Contraception (2021), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…(Note: numbers do not add to 423 because some articles included perspectives from multiple population groups.) Separate systematic reviews examining the values and preferences of women with specific reproductive health experiences (i.e., pregnant, postpartum, seeking emergency contraception, or seeking abortion) [9] , adolescents and young adults [7] , people living with HIV [10] , other end-users in specific circumstances (i.e., sex workers, transmasculine individuals, people who inject drugs, and those living in humanitarian contexts) [8] , and health workers [11] are published in this same journal issue.…”
Section: Resultsmentioning
confidence: 99%
“…(Note: numbers do not add to 423 because some articles included perspectives from multiple population groups.) Separate systematic reviews examining the values and preferences of women with specific reproductive health experiences (i.e., pregnant, postpartum, seeking emergency contraception, or seeking abortion) [9] , adolescents and young adults [7] , people living with HIV [10] , other end-users in specific circumstances (i.e., sex workers, transmasculine individuals, people who inject drugs, and those living in humanitarian contexts) [8] , and health workers [11] are published in this same journal issue.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have shown that partner opinion influences likelihood of contraceptive use (5,8,14,15,17,18). A study of South African university students found that women were more likely to use female condoms if their partner had a "positive attitude" toward the condoms (17).…”
Section: Discussionmentioning
confidence: 99%
“… 6 They can be discriminated against by health workers and other officials, and may be prevented from accessing care due to illegal migrancy status. 7–9 As with other marginalised communities, FSW may lack knowledge on their legal entitlements, may be unaware of where safe services are available, or may feel too stigmatised to request abortions from regulated services (if they are available). 10 , 11 Social networks have also been found to be instrumental in knowledge dissemination on unsafe abortion practices, and these may be particularly pronounced among marginalised FSW networks.…”
Section: Introductionmentioning
confidence: 99%